The International Court of Justice - Kolb, Robert; Perry, Alan (Lawyer) (Oxford : Hart Publishing, 2013)
This title, by an academic authority on international law who also appears as an advocate before the Court, examines the Statute of the Court, its procedures, conventions and practices.
Initial observations on the peaceful resolution of international disputes -- Origins and environment of the International Court of Justice at The Hague -- The texts governing the court's activities -- Composition of the court -- Contentious procedure : inter-state disputes -- General principles applicable to contentious proceedings -- Procedural aspects of contentious cases -- Advisory opinion procedure : opinions given to certain organs of, or affiliated to, the United Nations -- General principles governing the court's contentious and advisory procedures -- The court's jurisprudence and its current trends -- Miscellaneous questions -- Conclusion: The future of the International Court of Justice.
'Translated and lightly updated from the French original, R. Kolb, La cour international de justice (Paris, Pedone, 2013), by Alan Perry'--Half title page.
Includes bibliographical references (pages 1275-1281) and index.
In English and French.
Keywords: International Court of Justice -- Rules and practice; International Court of Justice